2007
DOI: 10.1111/j.1528-1167.2007.00988.x
|View full text |Cite
|
Sign up to set email alerts
|

Seizure‐Promoting Effect of Blood–Brain Barrier Disruption

Abstract: Summary:Purpose: It is generally accepted that blood-brain barrier (BBB) failure occurs as a result of CNS diseases, including epilepsy. However, evidences also suggest that BBB failure may be an etiological factor contributing to the development of seizures.Methods: We monitored the onset of seizures in patients undergoing osmotic disruption of BBB (BBBD) followed by intraarterial chemotherapy (IAC) to treat primary brain lymphomas. Procedures were performed under barbiturate anesthesia. The effect of osmotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
415
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 451 publications
(434 citation statements)
references
References 33 publications
(55 reference statements)
18
415
0
1
Order By: Relevance
“…Tissue samples of MTS have been shown to present a striking lack of peri‐vascular AQP4 water channels that mediates the glymphatic water clearance (Eid et al., 2005). The absence of AQP4 channels in MTS areas could lead to altered extracellular electrolyte concentrations that sensitizes neuronal tissue to seizures (Eid et al., 2005; Lundgaard et al., 2017; Marchi et al., 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Tissue samples of MTS have been shown to present a striking lack of peri‐vascular AQP4 water channels that mediates the glymphatic water clearance (Eid et al., 2005). The absence of AQP4 channels in MTS areas could lead to altered extracellular electrolyte concentrations that sensitizes neuronal tissue to seizures (Eid et al., 2005; Lundgaard et al., 2017; Marchi et al., 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Degradation of the BBB can occur after insults to the brain, including seizures (6,40,41). Serum albumin was detected by Western blot analysis in the PBS solution-perfused cortex four days following pilocarpine-induced SE in wild-type mice, compared with minimal albumin in saline solution-treated wild-type animals (Fig.…”
Section: Se (mentioning
confidence: 99%
“…Experimental evidence also supports a role of intravascular inflammation, often associated with BBB damage, in seizure disorders (Marchi et al, 2007a;Marchi et al, 2009;Seiffert et al, 2004;van Vliet et al, 2007). Recently, the association between circulating immune cells, their interaction with the BBB, and seizure propensity was proposed; leukocyte adhesion was shown to directly support ictogenesis in the pilocarpine model of seizures (Fabene et al, 2008).…”
Section: Blood-brain Barrier Dysfunction In Epilepsy: Experimental Anmentioning
confidence: 99%
“…After injury, local compromise of BBB integrity is common (Abbott et al, 2010;Cacheaux et al 2009;Oby and Janigro, 2006), as revealed by ultrastructural studies of animal and human epileptic tissue in multiple forms of epilepsy. Marchi et al, 2007a;van Vliet et al, 2007), and BBB opening may specifically serve as a trigger event leading to epilepsy. However, the research field has recently considered the fact that damage to the cerebral vasculature could be involved in the pathogenesis of seizures (Oby & Janigro, 2006).…”
Section: Blood-brain Barrier Dysfunction In Epilepsy: Experimental Anmentioning
confidence: 99%